THE PRIMARY INDICATORS OF AN AVERAGE RODUCTIVE ACTIVITY - B. P. Eliseev; Z. Lyu; I. P. Zheleznaja (Научный вестник МГТУ ГА, 2016)
The article deals with the primary productive indicators of an average airline activity that carries out passenger transportation to build up its system of quality. Four indicator groups are emphasized: the financial indicators, the indicators characterizing the quality of service to be provided, the indicators of air transportation quality, the indicators of personal operation quality. The algorithms to work out indicators are submitted.